Технология многокритериальной оценки иерархических структур для оценивания сценариев развития космической отрасли Украины - Колос, Л.Н.; Воронин, А.Н. (Проблемы управления и информатики, 2009)
Продемонстровано застосування технології багатокритеріальної оцінки ієрархічних систем для оцінки сценаріїв розвитку космічної галузі. Змодельовано ієрархічну систему для оцінки трьох гіпотетичних варіантів-альтернатив. Проведено порівняльний аналіз сценаріїв за допомогою отриманих аналітичних і якісних оцінок. The application of multicriteria evaluation of hierarchical systems technology for evaluating scenarios of space industry development is demonstrated. The problem is previously analyzed, a hierarchical system for evaluating 3 hypothetical variantsalternatives is simulated. A comparative analysis of scenarios using the obtained analytical and qualitative estimates is carried out.